2013
DOI: 10.1120/jacmp.v14i6.4074
|View full text |Cite
|
Sign up to set email alerts
|

Impact of MLC leaf width on volumetric‐modulated arc therapy planning for head and neck cancers

Abstract: This dosimetric study investigated the impact of multileaf collimators (MLC) leaf width in volumetric‐modulated arc therapy (VMAT) for head and neck cancers (HNC), either with a “standard” simultaneously integrated boost technique (S‐SIB) or with a “dose painting” SIB technique (DP‐SIB). HNC patients were planned either with an S‐SIB comprising three dose levels, from 56 to 70 Gy (16 patients), or with a DP‐SIB comprising five dose levels, from 56 to 84 Gy (8 patients), in 35 fractions. Two VMAT plans were cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Intuitively, a finer leaf width should result in more conformal target shaping. Lafond et al [22] showed that Beam Modulator (4mm leaf width) and MLCi2 (10 mm leaf width) MLCs from Elekta provided satisfactory dose distributions for head and neck cancer VMAT. OAR sparing was better for brainstem and spinal cord in Beam Modulator.…”
Section: Discussionmentioning
confidence: 99%
“…Intuitively, a finer leaf width should result in more conformal target shaping. Lafond et al [22] showed that Beam Modulator (4mm leaf width) and MLCi2 (10 mm leaf width) MLCs from Elekta provided satisfactory dose distributions for head and neck cancer VMAT. OAR sparing was better for brainstem and spinal cord in Beam Modulator.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the large leaf width of the ViewRay system (1-cm leaf width at 100-cm SSD) likely contributed to the worse reduced target conformity and lower dose gradients near the target volume in the tri-Co-60 IMRT plans than that in the VMAT plans with TrueBeam STx (0.25-cm inner leaf width at 100-cm SSD), as several studies have already shown decreased target conformity when using MLCs with large leaf widths. [21][22][23] Reviewing the results on normal tissue irradiation, the VMAT plans were also superior to the tri-Co-60 IMRT plans because of the lower penetrating power of the photon beams of the ViewRay system in comparison with a linear accelerator. Previous studies have demonstrated that low-energy photon beams increased body integral doses owing to the low penetrating power of the photon beams when treating thicker body parts.…”
Section: Discussionmentioning
confidence: 99%
“…4 As shown in the results, the beam-on time of the ViewRay system was much longer than that of VMAT because the delivery technique of the ViewRay system is static IMRT, which takes much longer than VMAT. 25,26 The long treatment time was also attributed to the low dose rate of the ViewRay system in comparison with the high dose rate of FFF photon beams (550 vs 2400 cGy min 21 at the depth of dose maximum). 27 Thus, the increased treatment time further indicated that the ViewRay system is inappropriate for spine SABR.…”
Section: Discussionmentioning
confidence: 99%
“…Quite a few studies have investigated the relationship between MLC leaf width and the quality of IMRT plans and have shown that finer leaf widths can result in more conformal dose distributions for target volumes and less dose delivered to normal tissue when the target volumes were small (Rodal et al, 2010;Shang et al, 2013;Hong et al, 2014). Similarly, few studies have shown the dosimetric advantage of using MLCs with narrow leaf width (Lafond et al, 2013;Park et al, 2016). However, there are very little data on the comparison of the dosimetric effect of narrow width MLC on the quality of IMRT and VMAT plans with simultaneous integrated boost techniques in our study setting.…”
Section: Is High Definition Mlc Dosimetrically Superior To Standard Dmentioning
confidence: 99%